Navigating the Local and the Translocal With Institutional Ethnography: Exploring Ethical Grey Areas in the Relationship Between Researcher and Standpoint Informants in Dementia Care Research - Nicole Dalmer; Guro Øydgard (Forum: Qualitative Social Research)
Institutional ethnography (IE) is grounded in the idea that the power structures shaping daily life—known as ruling relations—cannot be fully understood from any individual's immediate perspective. IE researchers, therefore, look beyond an individual's local environment and experiences to analyze how these broader ruling relations influence their everyday practices. Drawing on two complementary studies, we explore the practical and ethical challenges of identifying and mapping the ruling relations that connect local and translocal contexts for those conducting, teaching, or supervising IE research. The studies include a Norwegian project on family caregivers' access to formal health services and a Canadian investigation examining how family caregivers and paid staff manage information connected to dementia care. Based on experiences and insights from these projects, we identify three, key ethical grey areas in navigating between local and translocal contexts: 1. explaining IE concepts to informants with limited research knowledge; 2. handling data from distinct informant groups; and 3. producing findings that serve participants while potentially revealing uncomfortable knowledge about their institutions. We conclude by encouraging continued dialogue among IE researchers about the ethical complexities involved in such work.